2012
DOI: 10.1166/jnn.2012.5441
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Domain Wall Formation in Permalloy Nanowires with Geometric Pinning Sites

Abstract: An optimal geometric pinning site on Permalloy nanowires of varying widths has been investigated and applied in a magnetic memory scenario using micromagnetic simulations. Minimal limits on two key factors; the applied field length and the domain wall formation length are established such that vortex domain walls are reliably formed in the structures to facilitate lower powered domain wall movement using spin-polarised current. The symmetric wires with the nanoconstrictions at both sides have been found to fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The equation describes both the precession and relaxation motion of the magnetization in an effective field H . eff  The calculations were performed using Object Oriented MicroMagnetic Framework software [27], which uses an iterative process to solve the LLG equation for each cell of a finite element mesh [24].…”
Section: Micromagnetic Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The equation describes both the precession and relaxation motion of the magnetization in an effective field H . eff  The calculations were performed using Object Oriented MicroMagnetic Framework software [27], which uses an iterative process to solve the LLG equation for each cell of a finite element mesh [24].…”
Section: Micromagnetic Simulationsmentioning
confidence: 99%
“…These studies reported that wall mobility decreases linearly up to the critical field because the dynamic DW length also decreases with increasing field strength. Additionally, Willcox et al [24] simulated a number of permalloy nanowires with geometric pinning sites and found key design limits and some interesting observations, such as the formation of vortex DWs with small separations, showing that symmetric pinning sites are preferential to asymmetric sites. Being permalloy NWs Ni-rich systems, the work carried out by Leighton et al [25] on the reversal processes of asymmetric Ni nanowires contributes to better understand NiFe NWs when the behavior of both systems, concerning the coercive field and remanence magnetization as a function of the geometry and the angle at which the field is applied, needs to be compared.…”
Section: Introductionmentioning
confidence: 99%